2007
DOI: 10.1523/jneurosci.1215-07.2007
|View full text |Cite
|
Sign up to set email alerts
|

Evidence for Activity-Dependent Cortical Wiring: Formation of Interhemispheric Connections in Neonatal Mouse Visual Cortex Requires Projection Neuron Activity

Abstract: Neuronal activity plays a pivotal role in shaping neuronal wiring. We investigated the role of neuronal activity in the formation of interhemispheric (callosal) axon projections in neonatal mouse visual cortex. Axonal labeling with enhanced green fluorescent protein (GFP) was used to demonstrate spatially organized pattern of callosal projections: GFP-labeled callosal axons from one hemisphere projected densely to a narrowly restricted region at the border between areas 17 and 18 in the contralateral hemispher… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

34
250
0

Year Published

2007
2007
2016
2016

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 173 publications
(284 citation statements)
references
References 84 publications
(107 reference statements)
34
250
0
Order By: Relevance
“…Consistent with previous tracing studies, the authors observed that callosal projections in the contralateral hemisphere were restricted to a region between areas 17 and 18 with a strong enrichment of axon terminals in layers 1-3 and 5 ( Fig. 1 A) [Mizuno et al (2007), their Fig. 1 (http://www.jneurosci.org/cgi/content/ full/27/25/6760/F1)].…”
supporting
confidence: 86%
See 1 more Smart Citation
“…Consistent with previous tracing studies, the authors observed that callosal projections in the contralateral hemisphere were restricted to a region between areas 17 and 18 with a strong enrichment of axon terminals in layers 1-3 and 5 ( Fig. 1 A) [Mizuno et al (2007), their Fig. 1 (http://www.jneurosci.org/cgi/content/ full/27/25/6760/F1)].…”
supporting
confidence: 86%
“…The best characterized studies are of thalamocortical projections from the lateral geniculate nucleus to cortical layer 4, where cortical neurons are thought to go through an early phase of target selection dependent on molecular cues, followed by an activity-dependent mechanism, which then refines and maintains the connectivity (Katz and Crowley, 2002). In a recent The Journal of Neuroscience paper, Mizuno et al (2007) add another piece to the puzzle by showing that neuronal activity in callosal neurons is necessary for the initial laminar-specific elaboration of their axons.…”
mentioning
confidence: 99%
“…The synaptic source of the high synaptic binocularity of 2/3Ps and 5TPs could be the callosum. Indeed, callosal fibers branch mostly in layers 2/3 and 5 in rodent V1 (Jacobson and Trojanowski, 1974;Mizuno et al, 2007), and their inactivation reduces binoc- Figure 10. Differences in suprathreshold plasticity between 2/3Ps and 5TPs.…”
Section: Discussionmentioning
confidence: 99%
“…Previous studies using neuronal silencing with Kir2.1 have suggested that presynaptic activity plays a dominant role in axon branching (27,29,30). In particular, competitive interactions between a retinal ganglion cell and adjacent cells have been suggested to be crucial in retinotectal axon branching (27).…”
Section: Discussionmentioning
confidence: 99%